2017
DOI: 10.1002/app.45663
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the mechanism of enhanced crystallization of PLA in PLLA/PDLA mixture

Abstract: Poly(lactic acid) (PLA) is a bio-based and compostable polymer that has quickly developed into a competitive material, but the control of crystallinity is a bottleneck in extended utilization. The crystallization of PLA has been a rich topic because of the existence of two enantiomeric forms of poly(L-lactic acid) (PLLA) and poly(D-lactic acid) (PDLA) can form stereocomplex (SC) crystal with high melting point that can be used to control the crystallization behaviors. The SC crystal was regarded as an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…These scPLA films have been widely used in research, and are prepared by solution blending [7,8,11,15,16,17]. However, fabrication of scPLA films by melt processing is interesting, because of its possible use in industrial-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…These scPLA films have been widely used in research, and are prepared by solution blending [7,8,11,15,16,17]. However, fabrication of scPLA films by melt processing is interesting, because of its possible use in industrial-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…• , corresponding to diffractions of (110), (300/030), and (220) planes of stereocomplex crystal, respectively, which are the characteristic peaks of SC [36]. These results indicated that d-lactic units in PDLAG and PLLA could form SC through stereocomplexation [37].…”
Section: Xrd Analysis Of Sc-plga Crystal Structurementioning
confidence: 77%
“…All sc-PLAG samples only formed SC structure instead of HC structure, indicating that SC structure was superior to HC in sc-PLAG [33]. The preforming stereocomplex crystallite might act as nucleating agents in the blending process and significantly increase the crystallization rate of PLA [35,36]. We could also find from Table 2 that the melting point of sc-PLAG varied regularly with glucose content in feeding.…”
Section: Dsc Analysis Of Sc-plag Thermal Properties and Crystal Strucmentioning
confidence: 98%
“…No melting peak of PLLA/PDLA homo-crystallization at around of 170 °C was observed for all the blend nanofibers. T m of sc -PLA was reported to be 30–60 °C higher than that of individual PLLA and PDLA, which is attributed to the close packing of polymer chains, strong intermolecular interactions and consequently increased crystallinity [38,39,40,41] As shown in Figure 3a, the blends containing more than 5 wt % of sc -PLA show only one melting point at about 215 °C. This indicates electrostatic field applied in ESB process favor the formation of sc -PLA in PMMA nanofibers and is beneficial to improve the miscibility of sc- PLA and PMMA under certain conditions of sc -PLA content [42].…”
Section: Resultsmentioning
confidence: 99%